Validation of the School Maturity Test - Novović, Zdenka; Tovilović, Snežana; Jovanović, Veljko; Biro, Mikloš (Primenjena psihologija, 2009)
The purpose of this study is to examine psychometric properties of the School Maturity Test (SMT). The sample consisted of 149 children with average age of 81 months. The data were collected during regular testing of a school maturity in elementary schools in Šabac and Sremska Mitrovica. The results provided support for high reliability of SMT. Correlation between SMT and TIP- 1 (earlier test with same appropriation) global scores was 0.66, and high correlations were also obtained among subtests which were expected to measure similar constructs. Therefore, it was concluded that SMT displayed high concurrent validity. Furthermore, the predictive validity of SMT was examined in relation to teachers’ evaluation of cognitive functioning, conducted among first graders after their first term. The results showed excellent predictive validity of SMT subtests, among which Informations and Block design subtests reached the highest predictive power.